Processes influencing participation in the daily lives of immigrants living with polio in Sweden: A secondary analysis. Issue 2 (3rd April 2017) - Santos Tavares Silva, Iolanda; Thorén-Jönsson, Anna-Lisa; Sunnerhagen, Katharina S.; Dahlin-Ivanoff, Synneve
ABSTRACT: This paper explores and describes conditions influencing participation in daily occupations and how these interact with each other, in the daily lives of immigrants with late effects of polio. A secondary analysis of interviews with 12 immigrants from Eastern Africa now residing in Sweden was performed, using a grounded theory approach to probe deeper into the complexity of the concept of participation. This study highlighted that participation occurs through a participation process, which was identified as the core category. It emerged that participation took place through a complex dynamic interaction of subprocesses that contributed to value and identity development . The five subprocesses influencing participation in daily life were based on participants striving to achieve mastery of daily occupations, meaning in daily life, connection to places and people, belonging to groups, and trust of others. The findings indicate the need for awareness of the complexity, when conditions for participation are in question. With a deep understanding of participation as an interactional process with socioemotional meaning, both the individual and sociopolitical aspects of participation became evident. The intersection of disability and migration could lead to disadvantages and social exclusion within this population. These factors warrant consideration on an individual, a political and a social level. Politically, structures preventing and enabling participation must be considered. Similarly, attention must be paid to the social, and underlying conditions must be created in everyday meetings.